Pengaruh Stres Kerja, Motivasi dan Budaya Organisasi Terhadap Gaya Kepemimpinan Pada Guru Madrasah Aliyah (MAN) 1 Kabupaten Malang - Mery Asti Wulandari; Abdul Kodir Djaelani; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
ABSTRACTThis study aims to find out about how the leadership style in Madrasah Aliyah Negeri (MAN) 1 Malang Regency. In this study, the variables used to determine leadership style are using work stress, motivation and organizational culture. Based on data obtained from Madrasah Aliyah Negeri (MAN)1 Malang Regency, there are 47 teachers who meet the criteria or qualify as a research sample. Then, in determining this sample, researchers used a purposeful sampling method. That is, we decided on a sample based on certain criteria. Some also use the analytical method used, namely multiple linear regression analysis, ie research data in the form of panel data. The study found that work stress variables influence leadership style. Motivation variables have the same effect on leadership style. In addition, the cultural variables of the organization show the consequences that influence leadership style. Not only do these three variables affect simultaneously or together, but the consequences of work stress, motivation, and organizational culture affecting leadership style at the same time. Keywords : Leadership style, Job stress, Motivation, Organizational Culture